Exploring the Causes and Consequences of Restrictive Housing in America's Prisons and Jails, Colorado, Missouri, North Carolina, Oregon, 2015-2019 - Pitts, David ([Verlag nicht ermittelbar], 2023)
The overall purpose of this mixed methods, multi-site study was to explore the use of restrictive housing in United States prisons and jails from the perspective of incarcerated individuals and corrections officers who work in restrictive housing units. Restrictive housing, also known as solitary confinement or segregation, is defined as keeping an incarcerated person in their cell for 22 or more hours per day. To study the extent to which exposure to restrictive housing affects outcomes (i.e., mental/physical health problems, deterrence from future misconduct) for incarcerated individuals, the research team collected administrative records of housing moves ("stints") from the Colorado Department of Corrections and Missouri Department of Corrections. Records are available for all individuals incarcerated between January 1, 2015 and December 31, 2017. Data from Colorado includes roughly 1.3 million observations from 39,849 incarcerations. Data from Missouri includes roughly 1.1 million observations from 79,208 incarcerations. To study the impact of working in restrictive housing units on officers' physical, emotional, and mental wellbeing, the team administered surveys to officers working in correctional facilities in Missouri (n=376), North Carolina (n=249), and Oregon (site 1 n=47, site 2 n=133). The research team also conducted officer focus groups, interviews with agency leadership, observations of restrictive housing and general population units, and a national comprehensive survey about the use of restrictive housing in jails. Only the administrative records and officer wellbeing survey data are available in this collection.